The Effect of Company Size on Profit Management - Astri Linasmi (Pusat P2M Politeknik Negeri Batam, 2017)
The purpose of this study was to determine the effect of firm size on earnings management. The population in this study is the Indonesian Stock Exchange listed company in 2010-2014. The final sample was obtained 418 companies or 1.887 firm-year observation. The sample was selected using purposive sampling technique with some criteria. Research hypotheses were tested by multiple linear regression analysis. Based on test results, it was found that the financial leverage variable has a significant and positive impact to earnings management. The limitations of this research was only five years the company's data, does not include other variables that have a significant effect, as well as research using data of public companies.